2021
DOI: 10.1177/10915818211025477
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Assessment and Toxicokinetics of Apitegromab, an Antibody Targeting Proforms of Myostatin for the Treatment of Muscle-Atrophying Disease

Abstract: Myostatin is a negative regulator of skeletal muscle and has become a therapeutic target for muscle atrophying disorders. Although previous inhibitors of myostatin offered promising preclinical data, these therapies demonstrated a lack of specificity toward myostatin signaling and have shown limited success in the clinic. Apitegromab is a fully human, monoclonal antibody that binds to human promyostatin and latent myostatin with a high degree of specificity, without binding mature myostatin and other closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…A clinical trial on RO7204239 (GYM329) is about to start, while a clinical trial on apitegromab (SRK-015) is ongoing. Apitegromab is a fully human, monoclonal antibody that binds to human promyostatin and latent myostatin with a high degree of specificity, without binding mature myostatin and other closely related growth factors [ 142 ]. As discussed in the preceding section on preclinical studies, apitegromab in combination with an SMN upregulator was able to increase muscle mass and strength in SMA mice [ 97 ].…”
Section: Strategies To Modulate Myostatin and Their Applications In Mndsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial on RO7204239 (GYM329) is about to start, while a clinical trial on apitegromab (SRK-015) is ongoing. Apitegromab is a fully human, monoclonal antibody that binds to human promyostatin and latent myostatin with a high degree of specificity, without binding mature myostatin and other closely related growth factors [ 142 ]. As discussed in the preceding section on preclinical studies, apitegromab in combination with an SMN upregulator was able to increase muscle mass and strength in SMA mice [ 97 ].…”
Section: Strategies To Modulate Myostatin and Their Applications In Mndsmentioning
confidence: 99%
“…Before translating apitegromab into clinic, a comprehensive preclinical assessment of its pharmacology, pharmacokinetics, and safety across multiple species was performed. Safety studies conducted on monkeys and rats showed that weekly intravenous administration of apitegromab at high doses achieved sustained serum concentration and target engagement, in absence of tolerability issues and treatment-related adverse events [ 142 ]. No detrimental effects were observed on neurodevelopmental, motor, and reproductive outcomes in juvenile rats.…”
Section: Strategies To Modulate Myostatin and Their Applications In Mndsmentioning
confidence: 99%
“…Administration of eight weekly doses of apitegromab to cynomolgus monkeys also resulted in a dose-dependent (but not dose-proportional) response in accumulated latent myostatin. These apitegromab-induced increases in serum latent myostatin which were observed in animals [ 90 ], healthy volunteers [ 91 ] and patients with SMA (see below), are considered indicative of target (latent myostatin) engagement with apitegromab and complex formation of latent myostatin with apitegromab in the muscle that is ultimately reaching systemic circulation and measured in the serum [ 92 ].…”
Section: Introductionmentioning
confidence: 99%